Comparative Evaluation Of Amla, Neem Silver Nanoparticles Based On Anti Inflammatory And Cytotoxic Properties - P. Niharika; Sandhya Raghu (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: With the exponentially growing number of applications across various sectors, silver nanoparticles (Ag-NPs) have become one of the most sought-after nanoparticles as nanotechnology has advanced. Ag-NPs enhanced products could become more harmful to the environment and living things as a result of greater use.Materials and Methods: Extract preparation was prepared using neem leaves gathered from the university campus. To properly remove the dust and debris from the leaves' surface, they were extensively washed under running water. They were left in the hot air oven at 600C for 24 to 48 hours after being air dried for 10 days. Then, a fine powder was made from these leaves.And synthesis of nanoparticles and sample preparation for brine shrimp lethality assay was done.Results: The cytotoxic effect of amla and neem leaves mediated silver nanoparticles was evaluated in five different concentrations (10μL, 20 μL,30 μL,40 μL and 50 μL).Plant extract of silver nanoparticles revealed a high level of cytotoxicity and antiinflammatory properties .This demonstrates that the cytotoxic effect of amla and neem leaf extract-mediated nanoparticles is better even at 80 L . The collected data was tabulated into Microsoft office Excel 2013 transferred to SPSS version 26.0 software (SPSS, Chicago, IL, USA) for statistical analysis.Conclusion: According to our findings, the anti-inflammatory action of aloe vera and neem leaves, aided by silver nanoparticles, has nearly the same impact as traditional medicine and also shows minimal cytotoxicity. Within the limitations of this study we can conclude that this medication may be utilised as an alternative to diclofenac in the future.